Follow Math Help Forum on Facebook and Google+
Let me show you something similar. Perhaps apply it to yours. Let's show that Let u=g(x), then
i know this property. so we can directly deduce the conclusion from this property,right ????
I believe so. Give it a whirl.
still can get that result... can u show it explicitly?
here, i got g(x)= x, a= 0, " alt="=\frac{d}{dx}\int_{0}^{x}f(t)dt " /> =f(x)*g'(x)=f(x) cant continue...or i did =f(g(x)) * 1 integrate both sides , that integral= f(g(x)) * x, but how can u ignore g(x)=x?
View Tag Cloud